2023
DOI: 10.1021/acs.jcim.3c00358
|View full text |Cite
|
Sign up to set email alerts
|

Atomistic Picture of Opening–Closing Dynamics of DNA Holliday Junction Obtained by Molecular Simulations

Abstract: Holliday junction (HJ) is a noncanonical four-way DNA structure with a prominent role in DNA repair, recombination, and DNA nanotechnology. By rearranging its four arms, HJ can adopt either closed or open state. With enzymes typically recognizing only a single state, acquiring detailed knowledge of the rearrangement process is an important step toward fully understanding the biological function of HJs. Here, we carried out standard all-atom molecular dynamics (MD) simulations of the spontaneous opening–closing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 76 publications
0
7
0
Order By: Relevance
“…7A). A recent report demonstrated that variations of the standard AMBER forcefields better simulate spontaneous transitions in HJ conformations [58]. Thus, in our case, the AMBER bsc1 forcefield could be over stabilizing the central region through increased stacking interactions; however, we note that we still detect extensive distortions in structure and heightened dynamics (Fig.…”
Section: Discussionmentioning
confidence: 53%
“…7A). A recent report demonstrated that variations of the standard AMBER forcefields better simulate spontaneous transitions in HJ conformations [58]. Thus, in our case, the AMBER bsc1 forcefield could be over stabilizing the central region through increased stacking interactions; however, we note that we still detect extensive distortions in structure and heightened dynamics (Fig.…”
Section: Discussionmentioning
confidence: 53%
“…By contrast, for RNA and DNA in canonical duplexes, all‐atom force fields such as the parm99BSC0+χ OL3 [42] (abbreviated as OL3 in this publication) and parm99BSC1, [43] respectively, already give results that are in excellent agreement with experimental data [44,45] . MD simulations with validated force fields further enable the study of highly flexible systems [46,47] …”
Section: Introductionmentioning
confidence: 69%
“…These replica exchange methods have previously been used to mitigate the effects of strong solvation; for example, PT has been used to accelerate surface dehydration during the adsorption of a protein, while HREX has been used to scale the hydrophobicity of proteins in both implicit and explicit , solvents. These methods have also been combined with metadynamics to enhance configurational sampling, although current applications primarily focus on biomacromolecules. …”
Section: Introductionmentioning
confidence: 99%